Estimation of ionospheric reflection height using long wave propagation - D. Keuer (Advances in Radio Science, 2019)
Phase height measurements of low frequency radio waves are used to study the long-term variability of the mesosphere over Europe. Phase height measurements use a characteristic pattern in field strength registration of radio waves interpreted as phase relations between sky wave and surface wave to obtain the apparent height of the reflection point, the Standard Phase Height (SPH). Based on this SPH-method a homogenized daily series was generated since 1959 at Kühlungsborn. Improvements of the measuring method show that the signal is significantly influenced by lower atmospheric layers. Mesospheric reflection is not the exclusive source of the measured behavior. Tropospheric influence can not be neglected. Taking this into account one has to conclude that the strong coherency of the SPH data to mesospheric heights is not as significant as previously assumed.